Reinforcement of cell-mediated immunity driven by tumor-associated Epstein-Barr virus (EBV)-specific T cells during targeted B-cell therapy with rituximab - Tischer-Zimmermann, Sabine; Bonifacius, Agnes; Santamorena, Maria Michela; Mausberg, Philip; Stoll, Sven; Döring, Marius; Kalinke, Ulrich; Blasczyk, Rainer; Maecker-Kolhoff, Britta; Eiz-Vesper, Britta (Frontiers in Immunology, 2023)
In immunocompromised patients, EBV)infection or reactivation is associated with increased morbidity and mortality, including the development of B-cell lymphomas. The first-line treatment consists of reduction of immunosuppression and administration of rituximab (anti-CD20 antibody). Furthermore, the presence of EBV-specific T cells against latent EBV proteins is crucial for the control of EBV-associated diseases. In this study, we hypothesized that rituximab-mediated cell lysis leads to the release of EBV fragments from malignant infected B cells, and cross-presentation of these results in an enhanced EBV-specific effector T-cell response. To examine this hypothesis, EBV-infected B lymphoblastoid cell lines (EBV+ B-LCLs) as a model of EBV-associated lymphoma were treated with rituximab, resulting in cell lysates containing EBV antigens (EBV antigen-containing cocktail, EBV-AC). The efficiency of cross-presentation of these antigens by different antigen presenting cells and key characteristics of functional antiviral T cells, like activation and cytokine production, were investigated by interferon-γ (IFN-γ) EliSpot assay, multicolor flow cytometry, and multiplex analyses. EBV+ B-LCLs showed significantly less rituximab-mediated cell lysis compared with primary B cells. Moreover, EBV+ B-LCLs were found to cross-present exogenous antigens mainly through major histocompatibility complex (MHC) class I and elicited strong CD8+ cytotoxic T-cell responses. Stimulation also led to activation of CD4+ T helper cells, suggesting that longer peptide fragments are processed via the classical MHC class II pathway. Functional EBV-specific CD8+ effector memory T cells exhibited increased secretion capacity of cytotoxic effector molecules (IFN-γ, granzyme B, perforin). The expression of Tim-3, but not PD-1 and CTLA-4, was increased on stimulated T cells but had no negative effect on effector functions. The results of this study clearly demonstrate that, in addition to the known mechanism of rituximab-mediated lysis of infected malignant cells, cellular T-cell immunity can be established through the release of EBV antigens. This represents an efficient mechanism to improve treatment of CD20+ EBV-associated malignancies. This effect is also conceivable for further therapeutic approaches with other antibodies or even for the transfer of natural or genetically modified T cells, which specifically recognize and attack malignant cells and through their lysis lead to the release of the corresponding tumor antigens. .